WHAT’S NEW ABOUT THE NEW NATIONALISM? - John Farina (RUDN Journal of Philosophy, 2017)
What are the limitations of the New World Order created by the rise of transnational regimes and global business begun after the Second World War and reaching a crescendo in our new century? Are there limits to the proffered vision of globalization as a positive force, supported by its own set of mythologies and values? Is the so called New Nationalism or New Populism that in 2016 brought us Brexit in Europe and the election of Donald Trump in the United States a reaction to the excesses of the new world order? Are there any progressive aspects of those movements or are they fundamentally revanchist?